Is the «equivalent chlorpromazine» dose in psychopharmacotherapy consistent with Good Clinical Practice? - M. Yu. Popov; P. V. Kozlovskaya (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
Principles of adequate pharmacotherapy in psychiatry imply that shifting from one antipsychotic to another requires recalculation of the effective dose using the «chlorpromazine equivalent». The latter is deemed a reference measure for finding equally effective doses among antipsychotics. Given the molecular masses of the active substances and recommended drug doses, the association between the potential antipsychotic efficacy and the «complexity» of the molecules is analyzed in the present study. It is shown that the treatment efficacy is connected with the number of the substance molecules consumed with the certain drug dose. The lack of difference between «selective» and «non-selective» antipsychotics regarding association of their molecular masses and respective clinical activity challenges the suitability of the «chlorpromazine equivalent» for calculating antipsychotic doses. We assume that the approach based on the proportional ratio utilizing the highest drug dose recommended by the manufacturer is more adequate method of the antipsychotic dose estimation.